The Role of Classroom Management in the Learning Effectiveness of Madrasah Ibtidaiyah Students - Yusuf Rendi Wibowo; Fatonah Salfadilah (PGMI, STAI Miftahul Ula Nganjuk, 2026)
This study aims to describe the implementation and specific steps of classroom management in fostering learning effectiveness among fourth-grade students at Madrasah Ibtidaiyah Negeri 6 Bandar Lampung. The study employs a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation, with research subjects including classroom teachers and other relevant stakeholders. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings indicate that classroom management is implemented in a planned and comprehensive manner, encompassing classroom layout arrangement, seating organization, preparedness of instructional materials, selection of teaching methods, and the application of educative student discipline. Furthermore, the classroom management practices employed by teachers to enhance learning effectiveness include providing motivation prior to instruction, actively engaging students throughout the learning process, demonstrating strong mastery of subject matter, managing instructional time effectively, and applying discipline consistently and proportionately. These findings demonstrate that classroom management not only functions to maintain order but also plays a significant role in creating a conducive learning environment, increasing student engagement, and supporting character development. This study reinforces classroom management theory that positions teachers as managers of the learning environment and offers contextual contributions to classroom management practices in Madrasah Ibtidaiyah.